Evaluating travel time and passenger ridership of university shuttle bus service - Zulkefly, Nur Syahira; Kadar Hamsa, Abdul Azeez (Malaysian Institute of Planners, 2018)
Poor service adherence to the scheduled timetable and less service frequency during peak hours have contributed to unreliable shuttle bus services in International Islamic University Malaysia. As a result, students use either private vehicles or walk on-campus rather than riding the shuttle buses. This paper analyse travel time and passenger ridership of shuttle bus services from field surveys on journey time, running time, dwell time and passenger volume along Mahallah Ruqayyah and Mahallah Salahuddin shuttle bus routes. One of the key results on travel time indicates poor service adherence by bus service providers. In terms of passenger ridership, there was a huge gap between Mahallah Ruqayyah and Mahallah Salahuddin route where Mahallah Salahuddin has recorded a low passenger ridership even during peak hours. The findings also show that the service frequency of shuttle bus during peak hours cannot accommodate all students and therefore students either walk or use private vehicles to commute within campus area. Recommendations on the improvement of shuttle bus services are also discussed in this paper.